Bandwidth Management for Mobile Media Delivery - Mehrotra, Sanjeev; Chen, Hua; Jain, Sourabh; Li, Jin; Li, Baochun; Chen, Minghua (IEEE GLOBECOM 2012, 2012)
Mobile broadband networks using 3G and 4G technologies (such as EV-DO, HSPA, WiMAX, LTE) are rapidly becoming one of the prominent means to access the Internet. Multimedia consumption— requiring low delay, high bandwidth, or a combination of both—is projected to become a large portion of bandwidth utilization in mobile broadband networks. In this paper, we study the fundamental problem of how packet loss and delay vary as a function of the transmission rate over these networks. With extensive real-world measurement studies, we analyze the performance of a number of rate control algorithms commonly used in media transmission. We show that the variable nature of congestion signals (loss and delay) on these networks leads to an ultimate failure of existing rate control strategies to deliver adequate performance for multimedia applications. In addition, we show how a rate control algorithm derived from the utility maximization framework — which uses queuing delay as the primary congestion signal — can be modified to solve the challenging issues we have observed. By using a variable threshold to define when the network is congested, our proposed solution is able to achieve a significant improvement over algorithms that use fixed definitions of congestion.